Time- or State-Dependence? An Analysis of Inflation Dynamics using German Business Survey Data - Kai Carstensen; Heike Schenkelberg (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2011)
This paper evaluates the predictions of different price setting theories using a new dataset constructed from a large panel of business surveys of German retail firms over the period 1970-2010. The dataset contains firm-specific information on both price realizations and expectations. Aggregating the price data we find clear evidence in favor of state-dependence; for periods of relatively high and volatile inflation not only the size of price changes (intensive margin) but also the fraction of price adjustment (extensive margin) is important for aggregate inflation dynamics. Moreover, at the business cycle frequency, variations in the extensive margin explain a large fraction of inflation variability even for moderate inflation periods. This holds both for price realizations and expectations suggesting a role for state-dependent sticky plan models. Moreover, results from a structural sign-restriction VAR model show that the extensive margin reacts significantly to a monetary policy shock and is more important for the response of overall inflation than the intensive margin conditional on the shock. These findings confirm the validity of state-dependent pricing models that stress the importance of the extensive margin - even for low inflation periods.
urn:nbn:de:bvb:19-epub-12170-8
Keywords: E31; E32; E50; 330; Price setting behavior; time dependent pricing; state dependent pricing; monetary policy transmission; Inflation; Volatilität; Einzelhandelspreispolitik; Preismanagement; Zeit; Geldpolitische Transmission; Preisrigidität; Schätzung; Konjunkturumfrage; Deutschland